Obstructive Sleep Apnea Increases Sudden Cardiac Death in Incident Hemodialysis Patients - Kerns, Eric S; Kim, Esther D; Meoni, Lucy A; Sozio, Stephen M; Jaar, Bernard G; Estrella, Michelle M; Parekh, Rulan S; Bourjeily, Ghada (American journal of nephrology, 2018)
Mortality in end-stage renal disease (ESRD) occurs predominantly from cardiovascular disease (CVD) and sudden cardiac death (SCD). Obstructive sleep apnea (OSA) is characterized by periodic airflow limitation associated with sleep arousal and oxygen desaturation and is prevalent in patients with ESRD. Whether OSA increases the risk for SCD, cardiovascular and all-cause mortality among hemodialysis patients remains unknown. In a prospective cohort of 558 incident hemodialysis patients, we examined the association of OSA with all-cause mortality, cardiovascular mortality, and SCD using Cox proportional hazards models controlling for traditional CVD risk factors. Sixty-six incident hemodialysis patients (12%) had OSA. Mean age (56 years) and percentage of males (56%) were identical in OSA and no-OSA groups. Fewer African Americans had OSA than non-African Americans (9 vs. 18%, respectively). Participants with OSA had higher body-mass index, Charlson comorbidity score, and left ventricular mass index and greater prevalence of diabetes and coronary artery disease. During 1,080 person-years of follow-up, 104 deaths occurred, 29% of which were cardiovascular. OSA was associated with a higher risk of all-cause mortality (HR 1.90 [95% CI 1.04-3.46]) and cardiovascular mortality (HR 3.62 [95% CI 1.36-9.66]) after adjusting for demographics and body-mass index. OSA was associated with a higher risk of SCD after adjusting for demographics (HR 3.28 [95% CI 1.12-9.57]) and multiple cardiovascular risk factors. Incident hemodialysis patients with OSA are at increased risk of all-cause and cardiovascular mortality and SCD. Future studies should assess the impact of screening for OSA and OSA-targeted interventions on mortality in ESRD.